Plant Production Institute named after V. Iuryev as a Fonuder of Guidenes for Winter Wheat Varieties Breeding on arti Ficial Backgkounds in Ukraine (20s-80s of XX century) - В. В. Шелепов (Plant Varieties Studying and Protection)
The article highlights Kharkiv Breeding Facility, later referred to as Plant Production Institute named after V. Iuryev in 20s-80s concerning breeding the Winter Wheat in Ukraine and impact of the varieties obtained on th productivity increase. It is established that thanks to the efforts of V. Iuryev, V. Didus, M. Ielnikov, A. Shulyndina and others for the period of 1920s-1980s a number of economically valuable varieties have been created – Multrum 120, Iuryivka, Lutetsnes 266, Zenitka, Salut, Kharkivska 1, Kharkivska 32, Khar-kivska 81 and others. Thanks to efforts in breeding the yield index was growing gradually and reached the average level of 4,3 tons per hectare. In particular, in 1921–1930 – 2,33 ton/hectare, 1931–1940 – 2,42, 1941– 1950 – 3,01, 1951–1960 – 26,5, 1961 – 1970 – 4,3, 1971–1980 – 5,05, 1981–1990 – 4,47 t/hectare. In recompense for significant achievements in agricultural crops varieties breeding a breeding center was founded at the facilities of Plant Production Institute named after V Iuryev was founded in 1976.